In Situ Formation of Nano Ni–Co Oxyhydroxide Enables Water Oxidation Electrocatalysts Durable at High Current Densities. Issue 45 (20th September 2021) - Abed, Jehad; Ahmadi, Shideh; Laverdure, Laura; Abdellah, Ahmed; O'Brien, Colin P.; Cole, Kevin; Sobrinho, Pedro; Sinton, David; Higgins, Drew; Mosey, Nicholas J.; Thorpe, Steven J.; Sargent, Edward H.
Abstract: The oxygen evolution reaction (OER) limits the energy efficiency of electrocatalytic systems due to the high overpotential symptomatic of poor reaction kinetics; this problem worsens over time if the performance of the OER electrocatalyst diminishes during operation. Here, a novel synthesis of nanocrystalline Ni–Co–Se using ball milling at cryogenic temperature is reported. It is discovered that, by anodizing the Ni–Co–Se structure during OER, Se ions leach out of the original structure, allowing water molecules to hydrate Ni and Co defective sites, and the nanoparticles to evolve into an active Ni–Co oxyhydroxide. This transformation is observed using operando X‐ray absorption spectroscopy, with the findings confirmed using density functional theory calculations. The resulting electrocatalyst exhibits an overpotential of 279 mV at 0.5 A cm −2 and 329 mV at 1 A cm −2 and sustained performance for 500 h. This is achieved using low mass loadings (0.36 mg cm −2 ) of cobalt. Incorporating the electrocatalyst in an anion exchange membrane water electrolyzer yields a current density of 1 A cm −2 at 1.75 V for 95 h without decay in performance. When the electrocatalyst is integrated into a CO2 ‐to‐ethylene electrolyzer, a record‐setting full cell voltage of 3 V at current density 1 A cm −2 is achieved. Abstract : A scalable synthesis method of nanocrystalline metal selenides is developed to achieve both high activity and stability of electrocatalysts used for water oxidation, important for green hydrogen production. The formation of defective and coordinatively unsaturated sites by milling at cryogenic temperatures facilitates the hydration of metal sites to form active nanosized oxyhydroxides.